Improved Warehousing Performance Using the Frazelle Model in Pharmacies During a Covid-19 Pandemic - Syarif Hidayatuloh; Atik Febriani; Guntur Samodro; Titi Indarwati (Jurnal Ilmiah Teknik Industri, 2022)
In order for warehousing performance to remain at the standard, it is necessary to monitor the performance in the warehousing area, such as utilization and quality of goods in the warehouse, to increase the value of a company. Several drug retailers in Indonesia, especially in the Yogyakarta area, have not yet measured the performance of their warehousing activities, so it is not clear what improvements need to be made. With a comprehensive monitoring activity of warehousing activities, it can support the company to obtain helpful information that can help improve the performance of ongoing operations. This study was conducted to determine the performance position using the Frazelle model during the covid 19 pandemic in a drug retail business or pharmacy so that researchers can provide recommendations for improvements that can improve warehouse performance. The performance for the warehouse has a warehouse performance value of 55.60 and is included in the Average category. This recommendation can also be used as a benchmarking reference for other industries.